(3eaJGM GdWHs - (3Ydj Hf GdMSjf Hf eMeO Hf gfOh, CHh GdaQL,J (B420 (3g` s
(3ChdgG (B:s
(3bGd GdCSJGP CHh GdaQL Hf gfOh JUaM ENhGffG ef GdeJYdejf ebGdJi GdehSheI HGdeTQaI ai GdeONd Edi Yde GdadSaI aThbJge SghdI GdeCNP ajgG Edi ebGdI ai GdWH Ydi fgLgG eG CSZaJge HJUfjagG s
(3BNQgG (B:s
(3CjgG GdENhGf gPg NGJeI cJGH GdeaJGM bO hajfG VefGg ai UOQg hHd ChajfG Ydjg MJi NQL Yf MLe GdebGdI GdeTQaI s
(3GfXQgG eY GdeQTO Qbe (B" 730"s
(3fSNI KGdKI ecQQI Yf GdfSNI GdSGHbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B82s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B240 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B271 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs